Kualitas Simplisia Tanaman Biofarmaka Curcuma domestica Setelah Proses Pemanasan Pada Suhu Dan Waktu Bervariasi - Kusumaningrum, Hermin Pancasakti; Kusdiyantini, Endang; Pujiyanto, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Curcuma domestica is one of traditional medicinal plants that is found in Gunungpati Semarang. However the dried product do not achieve optimal standard quality for simplicia in terms of microbial contaminant and in an industrial scale household. Knowledge on how to use sterilization to produce better simplicia and reducing contaminant has not been known by farmers, yet. The purpose of this activity was to obtain the best heating treatment on sterilization of Curcuma simplicia using several temperature under sunlight and oven device. It was also want to show microbial growth after heating at several times and their influence on the quality of simplicia after treatment. The method was conducted by simplicia sterilization of C. domestica using sunlight sterilization for a week and using oven at a temperature of 300C, 400C, 500C and 600C for 1, 3, 6, 9, 12, 24, and 48 hours. The results showed that heating at temperature of 500C for 48 hours obtained the best simplicia, followed by heating at a temperature of 600C for 16-48 hours without contaminants after storing period for 3 months. Key words :Curcuma, sterilization, heat, microbia